Case report: Iatrogenic brachial artery dissection with complete anterograde occlusion during elective arterial line placement. (2018) - Weinberg, Laurence; Abu-Ssaydeh, Diana; Spanger, Manfred; Lu, Patrick; Li, Michael H.-G.
Highlights: Brachial arterial catheterisation is a safe and reliable procedure with a low risk of serious complications. Brachial arterial catheters provide a more accurate reflection of central aortic arterial pressure compared to their radial counterparts. In adults, brachial artery catheter related complications can be minimized by using smaller gauge catheters. Point of care ultrasonography can enhance diagnostic and procedural accuracy compared to a "blind-bedside" procedure. Postoperative neurological monitoring after brachial line catheterization should be routinely performed for timely identification and management of catheter complications. Abstract: Introduction: Brachial arterial catheters provide a more accurate reflection of central aortic arterial pressure compared to their radial counterparts. Although brachial arterial line complications are uncommon, we report a case of a rare iatrogenic brachial artery dissection with complete anterograde occlusion from elective arterial line placement. Presentation of case: A 41-year-old female presented for a right upper and middle lobe resection of a large neuroendocrine lung cancer. A brachial arterial line was inserted for continuous blood pressure monitoring using clinical landmarks. Six hours postoperatively the left hand was noted to be pale, cool and pulseless with complete paraesthesia. Thrombus was initially suspected on computed tomography angiography. Upon return to theatre, extensive dissection of the posterior brachial arterial wall was identified. Conclusion: We review our diagnostic pathway and treatment of this rare complication. Recommendations to minimise the risks of complications from brachial arterial line insertion are also overviewed. We recommend the routine utilization of ultrasound-guided technique and regular post-insertion neurovascular monitoring for the prevention and early recognition of complications from brachial artery catheter insertion.